Optimalisasi Literasi dan Kebahasaan Siswa Melalui Pendekatan Diferensiasi dalam Pembelajaran Teks Iklan, Slogan, dan Poster - Rahmat, Rahmat; Sulissusiawan, Ahadi; Apriyadi, Antonius Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to investigate the outcomes of enhancing literacy and language skills among eighth-grade students at MTs Negeri 2 Pontianak through the analysis of advertisements, slogans, and posters using a differentiated approach. The scope of this research includes understanding, interpreting, and creating relevant texts, as well as applying appropriate linguistic concepts within the context of the Merdeka Curriculum. This research is a classroom action study consisting of two cycles and employs a qualitative approach. The sample comprises 36 students from class 8.8, selected purposefully to explore their experiences and perspectives on literacy learning. Data were collected through in-depth interviews, classroom observations, and text document analysis. The findings indicate that the application of the differentiated approach is effective in improving students' literacy comprehension. Students demonstrated significant improvements in their analytical and creative text skills, as well as enhanced language proficiency. Interviews revealed that 75% of students felt more confident and motivated to express their ideas through text or reading, highlighting the positive impact of the implemented approach. The conclusion of this study emphasizes that the differentiated approach not only enhances literacy and language skills but also encourages active student engagement in the learning process. This suggests that teaching tailored to individual student needs can create a more positive learning experience. Therefore, educators are encouraged to implement this approach in their teaching and to adapt strategies that align with students' learning needs. Consequently, it is anticipated that learning outcomes will be more optimal and have a satisfying impact on students' literacy and language development in the future.